Hybrid-duplex systems for UAV communications under Rician shadowed fading - Tan, Ernest Zheng Hui (2020)
With the growing popularity of unmanned aerial vehicles (UAVs), spectrum management is a pressing issue, particularly for multi-UAV systems. To this end, a hybrid-duplex (HBD) UAV communication system (UCS) consisting of a full-duplex (FD) enabled ground station (GS), and legacy half-duplex (HD) UAVs is proposed in this paper. To model the fading and shadowing environment commonly encountered in UAV communications, a mix of Rician and Rician shadowed fading is assumed. In particular, novel power series approximations of the Rician shadowed fading power probability density function (PDF), and cumulative distribution function (CDF) are presented, along with closed-form outage probability expressions. Performance analysis shows that the proposed HBD-UCS exhibits lower outage probability than the HD-UCS when shadowing is encountered at low signal-to-noise ratios (SNRs). Also, inter-UAV interference has a stronger influence on outage probability decay at low SNR regimes, with lower inter-UAV interference corresponding to a sharper decline in outage probability.